From Technauriture to Cultauriture: Developing a Coherent Digitisation Paradigm for Enhancing Cultural Impac - Mostert, Andre; Lisney, Bob; Maroko, Geoffrey M.; Kaschula, Russell H. (International Journal of Society, Culture and Language, 2017)
Developing suitable frameworks and paradigms (theoretical and practical) is a challenge for all disciplines in the face of rapid technological changes. Technological advances are fundamentally changing discourse in many well-established areas of research; from advances in understanding the brain, questioning the informed wisdom of sectors of the brain, through to impacts of social networks on sociology, to digitisation of culture. Technology’s potential is a doubleedged sword which calls for coherent and reflective practices, to avoid the many pitfalls which abound. Kaschula recognised this as far back as 2004 in terms of orality, oral societies, and developed Technauriture as a framing solution. Drawing from this experience, the authors aim to expand the concept to offer a framing paradigm for culture in the form of Cultauriture. In this article the concept of Cultauriture is introduced and expanded to create a base for further research and dialogue with and between cultural practitioners, artists and policy makers.